Psychometric properties of the brief pain inventory modified for proxy report of pain interference in children with cerebral palsy with and without cognitive impairment. (July 2018) - Barney, Chantel C.; Stibb, Stacy M.; Merbler, Alyssa M.; Summers, Rebekah L.S.; Deshpande, Supreet; Krach, Linda E.; Symons, Frank J.
Abstract: Introduction: Cerebral palsy (CP) is the most common cause of physical disability in children and is often associated with secondary musculoskeletal pain. Cerebral palsy is a heterogeneous condition with wide variability in motor and cognitive capacities. Although pain scales exist, there remains a need for a validated chronic pain assessment tool with high clinical utility for use across such a heterogeneous patient population with and without cognitive impairment. Objectives: The purpose of this study was an initial assessment of several psychometric properties of the 12-item modified brief pain inventory (BPI) pain interference subscale as a proxy-report tool in a heterogeneous sample of children with CP with and without cognitive impairment. Methods: Participants (n = 167; 47% male; mean age = 9.1 years) had pain assessments completed through caregiver report in clinic before spasticity treatment (for a subgroup, the modified BPI was repeated after procedure). To measure concurrent validity, we obtained pain intensity ratings (Numeric Rating Scale of pain) and pain intensity, duration, and frequency scores (Dalhousie Pain Interview). Results: Modified BPI scores were internally consistent (Cronbach α = 0.96) and correlated significantly with Numeric Rating Scale intensity scores ( rs = 0.67, P < 0.001), Dalhousie Pain Interview pain intensity ( rs = 0.65, P < 0.001), pain frequency ( rs = 0.56, P = 0.02), and pain duration scores ( rs = 0.42, P = 0.006). Modified BPI scores also significantly decreased after spasticity treatment (pretest [scored 0–10; 3.27 ± 2.84], posttest [2.27 ± 2.68]; t (26) = 2.14, 95% confidence interval [0.04–1.95], P = 0.04). Conclusion: Overall, the modified BPI produced scores with strong internal consistency and that had concurrent validity as a proxy-report tool for children with CP.